Efektivitas Antibakteri Ekstrak Daun Binahong Anredera Cordifolia Pada Ikan Nila Oreochromis Niloticus Bleeker Yang Terpapar Bakteri Aeromonas Hydrophila - Shelly Pattipeiluhu; Stefanno Markus Anthony Rijoly; Christian Ernsz Pattipeilohy; Hadi Baharudin Saputra; Allyes Amarens P; Lekatompessy Lekatompessy (Syntax Corporation Indonesia, 2023)
Aeromonas hydrophila is a pathogen that has a negative impact on fish farming. Motile Aeromonas Septicemia (MAS) is a disease of tilapia caused by Aeromonas hydrophila bacteria. Binahong leaves (Anredera cordifolia) are used as an anti-bacterial agent against infected fish. This study aimed to determine the use of binahong leaf extract (Anredera cordifolia) as an antibacterial in tilapia (Oreochromis niloticus) infected with Aeromonas hydrophila. The results showed that a 10% concentration of binahong leaf extract was more effective in eliminating clinical symptoms than a 5% concentration. The results of this study also showed that as antibacterial, binahong leaf extract can cure tilapia disease as indicated by the normal percentage of lymphocytes, which is 60.00 – 65.7% compared to treatment without binahong leaf extract..